2020
DOI: 10.31883/pjfns/127635
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from Apples: Reviewing their Occurrence, Absorption, Bioavailability, Processing, and Antioxidant Activity – a Review

Abstract: and high environmental pollution. The consumption of fruits and vegetables is highly recommended to support the body in this respect. The main antioxidants found in fruits and vegetables are A, E, and C vitamins; β-carotene; lycopene; and a diverse group of compounds named phenolics. Therefore, it is hard to select one specific compound responsible for health benefits. That is why, Ohr [2004] stated that "scientists are currently studying how mixtures of antioxidants … work together. They are looking for syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 105 publications
(103 reference statements)
1
12
0
1
Order By: Relevance
“…Our study showed an initial pH close to 5.8 (in all batches) and this value decreased with time, amid a significant microorganism count increase. This agrees with that found by Jałosińska and Wilczak (2009) in meat balls, which indicated that for storage purposes it is important that meat reaches the lowest possible pH level to ensure meat shelf-life stability. In addition, pH during storage time was in accordance with the highest counts of lactic acid bacteria.…”
Section: Physicochemical Parameterssupporting
confidence: 91%
“…Our study showed an initial pH close to 5.8 (in all batches) and this value decreased with time, amid a significant microorganism count increase. This agrees with that found by Jałosińska and Wilczak (2009) in meat balls, which indicated that for storage purposes it is important that meat reaches the lowest possible pH level to ensure meat shelf-life stability. In addition, pH during storage time was in accordance with the highest counts of lactic acid bacteria.…”
Section: Physicochemical Parameterssupporting
confidence: 91%
“…Current research attributes the health benefits of apples mainly to the phenolic compounds which exhibit several biological functions beneficial for human health [54]. Apple phenolic compounds are believed to lower incidence of chronic conditions such as cardiovascular disease, cancer, asthma and pulmonary disease, diabetes, and obesity [49,[97][98][99][100][101][102][103].…”
Section: Health Benefits Of Apple Phytochemicals: Cancermentioning
confidence: 99%
“…Nevertheless, they are still needed for phenolic compounds in some concrete cases such as berries [ 75 ]. In other fruits, the bioavailability has recently been reviewed for apples [ 76 ] and tomatoes [ 77 ]. Finally, some authors have reviewed the effect of processing techniques on bioavailability and bioaccessibility in various bioactive compounds, reporting that, in general, HPP allows to increase both of them [ 78 ].…”
Section: Fruits and Their Antioxidant Activitymentioning
confidence: 99%